Antitumor Effect of Berberine Analogs in a Canine Mammary Tumor Cell Line and in Zebrafish Reporters via Wnt/β-Catenin and Hippo Pathways - Alessandro Sammarco; Giorgia Beffagna; Roberta Sacchetto; Andrea Vettori; Federico Bonsembiante; Giulia Scarin; Maria Elena Gelain; Laura Cavicchioli; Silvia Ferro; Cristina Geroni; Paolo Lombardi; Valentina Zappulli (Biomedicines, 2023)
The heterogeneous nature of human breast cancer (HBC) can still lead to therapy inefficacy and high lethality, and new therapeutics as well as new spontaneous animal models are needed to benefit translational HBC research. Dogs are primarily investigated since they spontaneously develop tumors that share many features with human cancers. In recent years, different natural phytochemicals including berberine, a plant alkaloid, have been reported to have antiproliferative activity in vitro in human cancers and rodent animal models. In this study, we report the antiproliferative activity and mechanism of action of berberine, its active metabolite berberrubine, and eight analogs, on a canine mammary carcinoma cell line and in transgenic zebrafish models. We demonstrate both in vitro and in vivo the significant effects of specific analogs on cell viability via the induction of apoptosis, also identifying their role in inhibiting the Wnt/β-catenin pathway and activating the Hippo signals with a downstream reduction in CTGF expression. In particular, the berberine analogs NAX035 and NAX057 show the highest therapeutic efficacy, deserving further analyses to elucidate their mechanism of action more in detail, and in vivo studies on spontaneous neoplastic diseases are needed, aiming at improving veterinary treatments of cancer as well as translational cancer research.